Literature review Characteristics and rationale for the clinical application of tricalcium silicate cement sealer - Z. S. Khabadze; O. S. Mordanov; I. M. Todua; S. M. Solimanov; S. A. Nazhmudinov; O. I. Magomedov; A. B. Adzhieva (Эндодонтия Today, 2020)
Bioceramics-based sealers were introduced to the market after bioceramic cements had appeared. Recently, lots of studies have been carried out regarding the physicochemical and biological properties of sealer such as BioRoot RCSTM based on tricalcium silicate cement. The properties of this material are close to the properties of dentin, which makes it applicable in endodontics. The aim of this literature review was to describe the properties of tricalcium silicate cement, its rationale and comparison with similar properties of sealers from various groups of materials.